Analisis Kepatuhan Wajib Pajak Usaha Mikro, Kecil dan Menengah (UMKM) Dalam Pemenuhan Kewajiban Perpajakan (Studi Kasus di KPP Pratama Bekasi Barat) Tahun 2021-2022 - Jiwa Pribadi; Dheivya Novita Sepia Anggie (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Taxpayer compliance can be defined as a state in which the taxpayer meets all tax obligations and implement taxation rights. Tax is a mandatory contribution to the state owed by an individual or entity of a coercive nature under the law, by obtaining reciprocity directly and used for state purposes for the greatest prosperity of the people. Micro Small aBusiness Medium Enterprises (MSMEs) are stand-alone aproductive abausiness units, carried out by individuals or business entities in all sectors of the economy. lack of level of compliance of MSME taxpayers in fulfilling tax obligations at the bekasi tax office West in 2021-2022 due to the socialization mechanism that is less accessible to all MSME elements. This research conducted to determine the compliance of Micro, Small and Medium Enterprises (MSMEs) taxpayers and obstacles and efforts made in the KPP Pratama Bekasi Barat in fulfilling tax obligations. This study uses qualitative research methods that are descriptive. Data collection from this study are interviews, observations and documentation. The results showed that analysis of MSME ataxpayer compliance in KPP Pratama Bekasi Barat in order to faulfill tax obligations is considered less effective MSME taxpayer coampliance when viewed from not achieving the revenue target in 2021 with a percentage of 35.7%. Lack of compliance of MSME taxpayers due to several obstacles that occur such as lack of knowledge and understanding of taxpayers, socialization that is less accessible, uneven and unscheduled, and limited facilities and infrastructure. Attempts what is done is to socialize with taxpayers with scheduled and created a tax kring phone number that can contacted the taxpayer to provide information.